(untitled) (Global Journal of Science Frontier Research, 2025)
Unity is defined as matter or a system with its maximum energy limit Unity Force is matter s tendency of being unity expressed as attracting while energy sharing in a unity or repelling while excessenergy releasing out of the unity The universe was and still is formed of four base particles proton electron neutrino and photon created from the Big Bang Then each electron bonded with a photon as an electron unity so that light could not propagate each proton bonded with a neutrino as a proton unity and the two unities made the universe opaque No gravity nor gravitational collapse is needed to draw these base particles together because they were dense and hot in the first place when created The high density and temperature were perfect for nuclear fusions and the force of nuclear fusion unity force would keep pulling particles together Most nuclear fusion centres with excess-energy releasing form stars and planets The rest extra-large nuclear fusion centres with inner cores unable to release excessenergy as a repelling force form black holes with much stronger attracting unity forces of their respective galaxies Nuclear fusion produced the first light and then atom formation brought the dawn of the universe